Loss of Cyp11c1 causes delayed spermatogenesis due to the absence of 11-ketotestosterone. Issue 3 (March 2020) - Zheng, Qiaoyuan; Xiao, Hesheng; Shi, Hongjuan; Wang, Tingru; Sun, Lina; Tao, Wenjing; Kocher, Thomas D; Li, Minghui; Wang, Deshou
Abstract : The impacts of androgens and glucocorticoids on spermatogenesis have intrigued scientists for decades. 11β-hydroxylase, encoded by cyp11c1, is the key enzyme involved in the synthesis of 11-ketotestosterone and cortisol, the major androgen and glucocorticoid in fish, respectively. In the present study, a Cyp11c1 antibody was produced. Western blot and immunohistochemistry showed that Cyp11c1 was predominantly expressed in the testicular Leydig cells and head kidney interrenal cells. A mutant line of cyp11c1 was established by CRISPR/Cas9. Homozygous mutation of cyp11c1 caused a sharp decrease of serum cortisol and 11-ketotestosterone, and a delay in spermatogenesis which could be rescued by exogenous 11-ketotestosterone or testosterone, but not cortisol treatment. Intriguingly, this spermatogenesis restored spontaneously, indicating compensatory effects of other androgenic steroids. In addition, loss of Cyp11c1 led to undersized testes with a smaller efferent duct and disordered spermatogenic cysts in adult males. However, a small amount of viable sperm was produced. Taken together, our results demonstrate that cyp11c1 is important for testicular development, especially for the initiation and proper progression of spermatogenesis. 11-ketotestosterone is the most efficient androgen in tilapia.